2015
DOI: 10.4137/cmt.s18865
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Associated Adverse Events

Abstract: Although statins are well tolerated, their widespread use has raised awareness of rare adverse events. For example, the United States Food and Drug Administration (FDA) has issued product label warnings about statin-associated myopathy, incident diabetes, and cognitive impairment. Additional statin-associated adverse effects include proteinuria, transaminitis, and hemorrhagic stroke. The underlying pathophysiology of these adverse events remains unclear, and thus little guidance exists on addressing these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…80 In contrast to above one observational study in unselected population of 7924 patients with hyperlipidemia (France) reported that 14.9% of patients receiving atorvastatin 40-80 mg experienced muscle symptoms 6 and the prevalence of muscle related adverse events was considered to increase 4 to 5 fold when dose of atorvastatin was increased from 40 to 80 mg. 80 A meta analysis of 19 randomized statin trials comparing standard doses of all statins except rosuvastatin accounted that fluvastatin was associated with the lowest rate of myopathy compared to other statin. 81 The rosuvastatin dose upto 40 mg have no muscle toxicity but the higher doses appeared to be associated with increased risk of myopathy.…”
Section: High Dose/ Individual Drug Effectmentioning
confidence: 90%
“…80 In contrast to above one observational study in unselected population of 7924 patients with hyperlipidemia (France) reported that 14.9% of patients receiving atorvastatin 40-80 mg experienced muscle symptoms 6 and the prevalence of muscle related adverse events was considered to increase 4 to 5 fold when dose of atorvastatin was increased from 40 to 80 mg. 80 A meta analysis of 19 randomized statin trials comparing standard doses of all statins except rosuvastatin accounted that fluvastatin was associated with the lowest rate of myopathy compared to other statin. 81 The rosuvastatin dose upto 40 mg have no muscle toxicity but the higher doses appeared to be associated with increased risk of myopathy.…”
Section: High Dose/ Individual Drug Effectmentioning
confidence: 90%
“…Although statins have revolutionized the treatment of hypercholesterolemia by inhibiting 3-hydroxy-3-methylglutaryl coenzyme-A reductase, some side effects of oral symptoms have been documented [ 5 8 ]. In another study [ 9 ], 17 out of 26 hypercholesterolemia patients between the ages of 50 and 70 with oral symptoms reported relief after controlled 7- and 15-day trials of the suspension of statins.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] However, widespread use of statins has also resulted in several reported adverse events including muscle symptoms, incident diabetes, and cognitive impairment. 6 Following review of the Adverse Event Reporting System database and other published literature in 2012, the US Food and Drug Administration (FDA) issued statin label warnings for reversible cognitive adverse events such as cognitive dysfunction, confusion, and memory impairment. 7 The correlation between intense LDL-C reduction and neurocognitive adverse events remains unclear, but a proposed mechanism is that the inhibition of cholesterol synthesis may affect the essential functions of neurons whose cell membranes and myelin consists of cholesterol and other lipids.…”
Section: Introductionmentioning
confidence: 99%